DINAMIKA KOMITMEN INTERNASIONAL DALAM KERANGKA PENGENDALIAN GLOBAL WARMING - Wijoyo, Suparto (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
Dynamic of commitment of International Community in the issueof control upon global warming has been developed since 1919up to present. From list of international treaties, it can be seenhow strong the commitment of global community in the issuesof environment, global warming as well as climate change.Unfortunately, it can be concluded, that those internationaltreaties is so fragmented and therefore, is difficult to beimplemented comparing with instrument of internationalenvironmental law in general. However, political will of nationalstate is the essence to create international agenda.